At høre det uhørte: Teologisk epistemologi som dialogisk livsorientering - Welz, Claudia (Dansk Teologisk Tidsskrift, 2023)
What does it mean to listen to what cannot be heard? In this article, the “unheard-of” is explored along two different tracks: (a) as something God-given or divinely revealed (in the context of theology and philosophy of religion) and (b) as something egregious or criminal (in the context of ethics and trauma studies). Theological epistemology is here developed with a special focus on the limits of the cognition and knowledge of God in Christianity (Anselm of Canterbury, Luther) and contemporary Judaism (Buber, Levinas), and on the significance of dialogue and second-person encounters. Epistemology is connected with a hermeneutics of the senses, where the human being is regarded as a witness who “listens” to something transcendent which can only be articulated on the basis of acoustic or auditory metaphors but nonetheless remains inaudible. In relation to an ethical and religious life-orientation (Kant, Stegmaier, etc.), listening is described as medio-passivity “in-between” activity and passivity, subjectivity and alterity. It is argued that the listener’s personal responsivity (Waldenfels) and responsibility (Buber, Levinas) remain opposed to “resonance” (Rosa) and an “echo” (Nancy) that has no distinct voice. Methodologically, epistemology as dialogical life-orientation is seen as part of a theory-practice feedback-loop which requires patient, hospitable listening practices in view of irresolvable theoretical tensions and fruitful paradoxes that always spur further thought.